2018
DOI: 10.3390/ijms19113560
|View full text |Cite
|
Sign up to set email alerts
|

Special Issue on Mechanisms of Mesothelioma Heterogeneity: Highlights and Open Questions

Abstract: This editorial aims to synthesize the eleven papers that have contributed to this special issue, where the mechanisms of mesothelioma heterogeneity have been tackled from different angles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…One limitation to the current study is that only a single MPM cell line was used for in vivo studies. As MPM is a heterogenous disease (60), future studies involving other mesothelioma cell lines or models may further delineate and expand on this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…One limitation to the current study is that only a single MPM cell line was used for in vivo studies. As MPM is a heterogenous disease (60), future studies involving other mesothelioma cell lines or models may further delineate and expand on this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, loss-of-heterozygosity (LOH) analysis demonstrated that the two areas of the chromosome most frequently altered in MPM are CDKN2A-ARF at 9p21, and NF2 at 22q12 [5,49,50]. CDKN2A encodes for a cell-cycle regulator mutated in more common cancers like melanoma, and neurofibromatosis 2 (NF2) acts as tumor suppressor that is part of the NF2/Merlin complex that makes up the NF2/Hippo pathway [51,52]. Deletions of 3p21 region, enclosing BAP1 gene are also reported in 33 MPM bioptic samples [53].…”
Section: Genetic Aspectsmentioning
confidence: 99%